ECOLOGICAL ASPECTS OF WEEDS IN COTTON FIELDS OF DISTRICT LASBELA BALOCHISTAN, PAKISTAN. - Baloch, A. Hameed; Ahmed, Imtiaz; Ahmed, Saeed; Buzdar, M. Aslam- (Hanken, 2015)
The present study pertains to assess the composition of weed communities in cotton (Gossypium hirsutum) fields of District Lasbela, Balochistan. Assessments were made in terms of species composition, and distribution in different areas of Lasbela District. Plant communities in cotton crop systems were evaluated in terms of relative frequency, relative cover, relative density and importance index for each species. Study areas were also compared in terms of species diversity by the Sampson’s diversity index. Forty-one weed species were reported from the study area of which ten belonging to monocot families, and thirty-one to dicot families. The most common weeds were Cyperus rotundus (I.V. 44.89±7.18), Cynodon dactylon (I.V. 38.60±9.34), Panicum capillare (I.V. 37.52±14.98), Euphorbia prostrata (I.V. 29.08±6.25) Cressa cretica (I.V. 24.46±14.16), and Trianthema portulacastrum (I.V. 23.15±6.84). There is also evidence that some weed species are more favored by specific field conditions such as salinity, although the causes of this selective behavior are not fully studied in this paper. The presence of Cressa cretica with higher importance value index (24.46±14.16) clearly indicated the presence of salinity in these study areas.